Bacterial Infections of the Central Nervous System - LaPenna, Paul A.; Roos, Karen L. (Seminars in Neurology, 2019)
Acute bacterial meningitis and spinal epidural abscess are neurological emergencies. Acute bacterial meningitis may present with symptoms as nonspecific as headache and fever, but rapid progression to an altered level of consciousness is not unusual. Spinal epidural abscess manifests initially as back pain, followed by radicular pain, then weakness, and finally paraplegia. Brain abscess may initially present only with headache, or as a new-onset seizure or with a focal neurological deficit. Bacterial infections of the central nervous system require emergent diagnosis and management. In this article, the pathogenesis, etiological organisms, diagnostic studies, differential diagnosis and management of acute bacterial meningitis, spinal epidural abscess, and brain abscess are discussed.
Keywords: acute bacterial meningitis; spinal epidural abscess; brain abscess